Superhelical DNA studied by solution scattering and computer models - Langowski, Jörg; Klenin, Konstantin; Tóth, Katalin (Genetica, 1999)
We present here recent results on the structure of superhelical DNA and its changes with salt concentration between 0.01 and 1.5 M NaCl. Scattering curves of two different superhelical DNAs were determined by static light scattering. The measured radii of gyration do not change significantly with salt concentration. Small-angle neutron scattering, together with calculations from a Monte Carlo model, allows to determine the superhelix diameter. Measured and simulated scattering curves agreed almost quantitatively. Experimentally we find that the diameter decreases from 16.0±0.9 nm at 10 mM to 9.0±0.7 nm at 100 mM NaCl. The superhelix diameter from the simulated conformations decreased from 18.0±1.5 nm at 10 mM to 9.4±1.5 nm at 100 mM NaCl. At higher salt concentrations up to 1.5 M NaCl, the diameter stays constant at 9 nm.
Gesehen am 23.04.2021